Sosialisasi Pilah Sampah dari Rumah (PILSADAR) di Rukun Tetangga (RT) 06 Lingkungan Sembalun Perumahan Lingkar Permai Kota Mataram - Aminullah, Aminullah; Kholisussa’di, Kholisussa’di; Hunaepi, Hunaepi; Samsuri, Taufik; Karmana, I Wayan; Haerazi, Haerazi; Sukarma, I Ketut (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of this service is to provide understanding and awareness to the residents of the Neighborhood Rukun Tetangga (RT) 06 in Sembalun Environment, Lingkar Permai Housing, Mataram City about waste management and processing through the Sorting Garbage from Home (PILSADAR) program. Partners in this activity are residents of the Neighborhood Association (RT) 06 Sembalun neighborhood, Lingkar Permai Housing, Mataram City, totaling 20 residents. The implementation of the service uses the Participatory Rapid Appraisal (PRA) approach with the stages of activities, namely: 1) planning; 2) implementation; and 3) evaluation. The results of these activities have had a positive impact on increasing public understanding and awareness of the community participation-based waste management paradigm through the PILSADAR program. Socialization activities need to be continued with training activities on waste management, both organic and inorganic so that people can manage their own waste from home.